Ferroelectric properties and leakage current characteristics of Bi3.25La0.75Ti3O12 thin films prepared by the polymeric precursor method - Simoes, A. Z. (2005)
The ferroelectric properties and leakage current mechanisms of preferred oriented Bi3.25La0.75Ti3O12 (BLT) thin films deposited on La0.5Sr0.5CoO3 by the polymeric precursor method were investigated. These films showed excellent ferroelectric properties in terms of large remnant polarization (2P(r)) of 47.6 mu C/cm(2) and (2E(c)) of 55 kV/cm, fatigue-free characteristics up to 10(10) switching cycles, and a current density of 0.7 mu A/cm(2) at 10 kV/cm. X-ray diffraction and scanning electron microscope investigations indicate that the deposited films exhibit a dense, well-crystallized microstructure having random orientations and with a rather smooth surface morphology. The improved ferroelectric and leakage current characteristics can be ascribed to the platelike grains of the BLT films, which make the domain walls easier to be switched under external field.